The Invention of the Brazilian Northeast - Albuquerque Jr., Durval Muniz de (Albuquerque Júnior) (Book collections on Project MUSE., 2014)
One of Brazil's leading historians denaturalizes the country's Northeast, showing when, by whom, and for what reasons the region was invented as a region with a particular identity.